Malignant Metastatic Insulinoma in a Dog - Ozmen, Ozlem; Sirin, Yusuf Sinan (Acta Scientiae Veterinariae, 2016)
Background: Insulinomas are tumors of the pancreatic islet beta cells that secreting insulin. They are malignant neoplasms and rarely seen in dogs. Because insulinomas secrete excessive insulin and hypoglycemia occur. The most common clinical symptoms are seizures, extreme weakness, and other neurological abnormalities. The tumors typically release insulin episodically, with clinical signs being seen intermittently as a result. These are most often associated with prolonged starvation or prolonged periods of exertion. Insulinoma occurs most often in middle-aged and older dogs, averaging nine years in age. They affect both sexes and are more likely in larger breeds. The most commonly afﬂicted breeds are German Shepherds, Irish Setters, Boxers, Golden Retrievers and Terriers. Case: In this study, a case of malignant insulinoma with multiorgan metastasis in a 7-year-old hunting dog that brought to the clinic with complaints of constipation and inappetence were evaluated by clinical, cytological, histopathological and immunohistochemical fndings. Owner stated that the animal suffers from constipation for 4 days, but no vomitus or nervous symptoms were present. Clinical efforts not solved the constipation. For to the defnitive diagnosis the dog decided to underwent laparotomy. After a midline abdominal approach multiple whitish, hard and irregular metastatic tumoral masses were observed in different abdominal organs. Because of the poor prognosis and according to owner’s acceptance the dog euthanatized at the same time. At necropsy, a bloody serous ﬂuid approximately 500 mL was found in the abdominal cavity. The intestines were hyperemic and hemorrhagic in some areas. A hemorrhagic 9x5x3 cm in diameter mass was observed on the pancreas. Mesenterial adhesions were formed due to mass between duodenum and jejunum. The mass was moderately hard and cut surface was bloody, necrosis was observed in some areas. At the gross examination, whitish color, various sized and multiple metastatic masses were noted in spleen, liver, lymph nodes and lungs. Before formalin fxation, impression smears were made from the pancreatic mass. In cytological preparations of the lesion, epithelial cells in different shapes and sizes were observed. At the histopathological examination, the tumor mass consisted of anaplastic, pleomorphic cells that have pale cytoplasm, vesicular nucleus and prominent nucleolus. Diffuse necrotic areas were noted in the mass. Similar metastatic masses were seen in liver, spleen, lungs and kidneys. The tumor cells were positive for insulin and negative for glucagon immunohistochemically. Discussion: Insulinomas generally caused nervous symptoms due to hypoglycemia. Metastasis may occur in some cases and generally lymph node metastasis occurs. Spleen metastasis are very rare in insulinoma cases. The mean age of the occurrence of insulinoma is generally older than 9-year-old. In this case, a case of malignant insulinoma with multiorgan metastasis and caused constipation due to intestinal adhesions in a dog was presented with clinical and pathological fndings. Best of the author’s knowledge insulinoma as a cause of constipation not previously reported in a dog. The aim of this study was to report a case of metastatic insulinoma without neurological symptoms but constipation in a 7 years old hunting dog by clinical, pathological, cytological and immunohistochemical fndings. Keywords: Malignant insulinoma, constipation, cytology, histopathology, immunohistochemistry, dog.